If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3) + (3x + 2) = 4 Reorder the terms: (-3 + x) + (3x + 2) = 4 Remove parenthesis around (-3 + x) -3 + x + (3x + 2) = 4 Reorder the terms: -3 + x + (2 + 3x) = 4 Remove parenthesis around (2 + 3x) -3 + x + 2 + 3x = 4 Reorder the terms: -3 + 2 + x + 3x = 4 Combine like terms: -3 + 2 = -1 -1 + x + 3x = 4 Combine like terms: x + 3x = 4x -1 + 4x = 4 Solving -1 + 4x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4x = 4 + 1 Combine like terms: -1 + 1 = 0 0 + 4x = 4 + 1 4x = 4 + 1 Combine like terms: 4 + 1 = 5 4x = 5 Divide each side by '4'. x = 1.25 Simplifying x = 1.25
| 7x-3=5x+6-3 | | 41.2x+49.8-26.1x-30.1= | | T/0.3=1.7/0.9 | | 32-(30-4)= | | x+5x=500 | | -3/4xx=-27 | | 6+3u=12 | | 2/0.21=8-n | | 4t-24=28 | | 2x-8+6-x=4+10 | | 8/13=8/n | | 19/20x=36 | | 5(x-2)+2(x+5)= | | .25x-12=x+3 | | 70+60(8x+2)=180 | | 3x+42=9.5 | | 3(2x+1)-2(x+5)= | | (X-7/3)=9 | | 3-4(2-3x)=2(6x-2) | | Y=5y+6 | | 1/2z=15 | | 5z-3/4(8z-4)=-1 | | -2x-3+5x+2= | | 4ln(4x)+2=10 | | 7/10=m/4 | | -4K+2=-14 | | 3e^4x=1338 | | 5=4p-7 | | x-7/3=9 | | -4K+2=-12 | | 7x+4x+8x=0 | | -2a+20+9a=5a-8a |